Partial lipoatrophy with insulin resistant diabetes and hyperlipidaemia (Dunnigan syndrome). - Burn, J (1986)
A family is presented in which at least five members in three generations suffered a characteristic syndrome of generalised lipoatrophy, sparing the head and neck, and muscle hypertrophy variably associated with high plasma insulin and lipid levels and insulin resistant diabetes. This pedigree contains the first documented affected male with the syndrome. The diagnosis is of practical importance since close medical supervision of asymptomatic gene carriers is likely to improve their prognosis. The findings in this family have relevance also to the study of insulin and lipid metabolism.